Effect of Once-Daily Generic Ciclesonide on Exhaled Nitric Oxide in Atopic Children with Persistent Asthma - Mallol-Villablanca, E; Aguirre-Camposano, V; Gallardo-Fernandez, A; Riquelme-Baez, C; Sanchez-Villa, C (Elsevier Doyma, 2016)
Background: Ciclesonide (CIC) is an effective inhaled corticosteroid for treating asthmatic children. However, its effect on airway inflammation assessed by the fraction of exhaled nitric oxide (FENO) in children with persistent asthma is virtually unknown. We aimed to assess the effect of once-daily generic CIC, 80 or 160 μg, on FENO, lung function, asthma control and bronchial hyperresponsiveness, in atopic children with persistent asthma. Methods: This was a 12-week, randomised, double-blind, parallel-group study. Sixty children with mild-to-moderate persistent asthma were recruited. Changes in FENO, asthma control score, lung function (FEV1) and bronchial hyperresponsiveness to methacholine (BHR) were used to assess the effects of both CIC doses. Non-normally distributed variables were log-transformed to approximate normality, and parametric tests were used for comparisons within and between groups at baseline and after 12 weeks of treatment. Results: In the CIC 80 μg group, FENO decreased from 45.0 ppb (95% CI 37.8-53.7) to 32.7 ppb (95% CI 21.0-47.3) at the end of study (P = 0.021), whereas in the CIC 160 μg group, FENO decreased from 47.3 ppb (95% CI 40.4-55.3) to 30.5 ppb (95% CI 24.1-38.7) (P < 0.001). The difference between groups in FENO at the end of study was not significant (P = 0.693). There was a significant improvement of asthma control with both CIC doses but there was no significant change in BHR or FEV1 in either group. Conclusion: Once-daily generic ciclesonide (80 μg or 160 μg), for 12 weeks, is effective to improve airway inflammation and asthma control in atopic children with persistent asthma. © 2014 SEICAP.